2013
DOI: 10.1088/0029-5515/53/7/073040
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of ICRF waves and axial transport of high-energy ions owing to spontaneously excited waves in the GAMMA 10 tandem mirror

Abstract: Plasmas with high ion-temperature of several keV and strong temperature anisotropy of more than 10 have been produced by using ion-cyclotron range of frequency (ICRF) heating in the GAMMA 10 tandem mirror. In such high performance plasmas with strong anisotropy, high-frequency fluctuations, so-called Alfvén-Ion-Cyclotron (AIC) waves, are spontaneously excited. The AIC waves have several discrete peaks in the frequency spectrum. Couplings between ICRF waves for heating and excited AIC waves are clearly observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…The reflectometer has already shown its usefulness especially on nonlinear phenomena occurring inside the hot plasma; a magnetic probe installed at periphery has less sensitivity for such phenomena compared with the reflectometer. Enhanced wave-wave couplings between ICRF waves including the AIC waves have been observed along with the saturation of confined energy [4]. Bispectral analysis applied to fluctuation data obtained by the reflectometer showed that the difference frequencies between the discrete AIC frequencies were produced by wave-wave coupling between the AIC waves with radial dependence; stronger coupling occurred near the core region [5].…”
Section: Introductionmentioning
confidence: 99%
“…The reflectometer has already shown its usefulness especially on nonlinear phenomena occurring inside the hot plasma; a magnetic probe installed at periphery has less sensitivity for such phenomena compared with the reflectometer. Enhanced wave-wave couplings between ICRF waves including the AIC waves have been observed along with the saturation of confined energy [4]. Bispectral analysis applied to fluctuation data obtained by the reflectometer showed that the difference frequencies between the discrete AIC frequencies were produced by wave-wave coupling between the AIC waves with radial dependence; stronger coupling occurred near the core region [5].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed description of GAMMA 10/PDX has been provided elsewhere [1][2][3][4][5][6][7][8][9][10][11][12]. The magnetic field strength at the midplane of the central cell is 0.405 T, and the mirror ratio of the central cell is 5.…”
Section: Methodsmentioning
confidence: 99%
“…A microwave reflectometer (RM) was constructed for studying high-frequency fluctuations in the plasma core region [9]. This system consists of two simple heterodyne reflectometers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An understanding of the wave-particle interactions that cause the axial transport of the high-energy ions and an assessment of a) Electronic mail: ikezoe@prc.tsukuba.ac.jp the nonlinear phenomena that may be related to the observed heating efficiency degradation would also be helpful. 11,12 For all the research described above, a multi-point measurement system that can obtain the amplitude and phase profiles of these high-frequency small-amplitude fluctuations is required.…”
Section: Introductionmentioning
confidence: 99%